On the influence of beryllium impurities on the transport properties of multicomponent arc plasma - Porytskyy, P.V. (Вопросы атомной науки и техники, 2014)
The influence of beryllium impurities on the transport properties of multicomponent arc plasma is considered in the ambient atmosphere of argon and carbon dioxide. The calculations are carried out on the base of Grad’s method, and it is shown that a small amount of metal causes the essential changes in the values of transport coefficients in comparison with the case of pure gaseous mixtures. It is revealed that the influence of the Ramsauer effect on transport properties can be neutralized by additions of metal into ambient argon.